Phytochemicals and Larvicidal Activity of Sonneratia alba Root Extracts from Ngurah Rai Mangrove Forest, Denpasar-Bali - Wijaya, Made Dharmesti; Indraningrat, Anak Agung Gede; Kirtanayasa, I Gede Yoga Ayuning (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Dengue is an endemic disease with a high incidence in almost all Southeast Asian countries, including Indonesia. This infectious disease is caused by a virus transmitted by the bite of Aedes aegypti mosquito as the main vector. Effective mosquito vector control is a crucial step in stopping the spread of this virus. Of the several methods available, the use of larvicides is considered one of the most successful treatments in reducing the number of mosquito vectors. However, widely used synthetic larvicides can have undesirable side effects on the environment and non-target organisms including human health. The aim of this study was to discover a new biolarvicide from natural materials that is relatively safer. In this study, the biolarvicidal activity of mangrove plant species that are commonly found in Ngurah Rai Mangrove Forest Bali was tested, namely Sonneratia alba. Mangrove root simplicia was extracted by reflux method using three different solvents namely methanol, chloroform, and n-hexane. The content of compounds in the extract were analyzed using GC/MS method. The larvicidal activity of the extracts were tested on A. aegypti instar III/IV larvae with concentrations of 0.1, 1, 10, 100, and 1000 ppm for 24 hours. Subsequently, the average value of larval mortality was used to calculate the LC50 of each extract. The results showed that S. alba methanol extract provided the best larvicidal activity compared to chloroform and n-hexane extracts, with mortality of 69.33% at a concentration of 1000 ppm and LC50 of 1265 ppm. GC-MS analysis showed that the methanol extract of S. alba contained five dominant compounds namely Methyl 2-hydroxy-eicosanoate (19.55%); 4H-1-Benzopyran-4-one, 3,5-dihydroxy-2-(4-hydroxy-3-methoxyphenyl)-7-methoxy (16.48%); 4-((1E)-3-Hydroxy-1-propenyl)-2-methoxyphenol (10.06%); Benzamide, N-[4-(2-naphtyl)-2-thiazolyl]- (9.40%); and 2,3-Dihydro-3,5-bis(3-methoxyphenyl)-1H-inden-1-one (6.52%). The results of this study provide a preliminary result on larvicide activity from mangrove S. alba in order to develop bio larvicides from nature which is safer for human health and environment.